2019
DOI: 10.31744/einstein_journal/2020ao4739
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of injuries due to ankle sprain diagnosed in an orthopedic emergency room

Abstract: Objective To use magnetic resonance imaging to assess the prevalence of foot and ankle ligament injuries and fractures associated with ankle sprain and not diagnosed by x-ray.Methods We included 180 consecutive patients with a history of ankle sprain, assessed at a primary care service in a 12-month period. Magnetic resonance imaging findings were recorded and described.Results Approximately 92% of patients had some type of injury shown on the magnetic resonance imaging. We found 379 ligament injuries, 9 osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
3
9
0
8
Order By: Relevance
“…Other musculoskeletal structures, such as some tendons (flexor hallucis longus, flexor digitorum longus, extensor hallucis longus, extensor digitorum longus, tibialis posterior, tibialis anterior, peroneus longus and brevis tendons, and plantar fascia), ligaments (PTFL, anterior tibiofibular ligament, tibiotalar ligament, SL, and deltoid ligament), and the talocalcaneal joint, did not show any relationship with ATLF injuries. Our findings regarding these musculoskeletal structures are in line with prior research (2,38), except that a previous study observed correlations between lateral ligament complex injuries and syndesmosis and deltoid injuries (38) and we did not. A possible explanation of these controversial findings may be that our study was carried out in a podiatric outpatient clinic, whereas the other study was performed in an orthopedic emergency room (38).…”
Section: Non-association Between Tendon Ligament and Joint Conditions And Atfl Injurysupporting
confidence: 93%
See 2 more Smart Citations
“…Other musculoskeletal structures, such as some tendons (flexor hallucis longus, flexor digitorum longus, extensor hallucis longus, extensor digitorum longus, tibialis posterior, tibialis anterior, peroneus longus and brevis tendons, and plantar fascia), ligaments (PTFL, anterior tibiofibular ligament, tibiotalar ligament, SL, and deltoid ligament), and the talocalcaneal joint, did not show any relationship with ATLF injuries. Our findings regarding these musculoskeletal structures are in line with prior research (2,38), except that a previous study observed correlations between lateral ligament complex injuries and syndesmosis and deltoid injuries (38) and we did not. A possible explanation of these controversial findings may be that our study was carried out in a podiatric outpatient clinic, whereas the other study was performed in an orthopedic emergency room (38).…”
Section: Non-association Between Tendon Ligament and Joint Conditions And Atfl Injurysupporting
confidence: 93%
“…Our findings regarding these musculoskeletal structures are in line with prior research (2,38), except that a previous study observed correlations between lateral ligament complex injuries and syndesmosis and deltoid injuries (38) and we did not. A possible explanation of these controversial findings may be that our study was carried out in a podiatric outpatient clinic, whereas the other study was performed in an orthopedic emergency room (38). Ziai et al analyzed the influence of the peroneus longus as passive ankle stabilizer in lateral sprains being closing that the peroneus longus tendon assume the role of stabilizer in ankle sprains (44).…”
Section: Non-association Between Tendon Ligament and Joint Conditions And Atfl Injurysupporting
confidence: 93%
See 1 more Smart Citation
“…Despite its excessive prevalence, the long-term prognosis of an acute ankle sprain is not favorable and a high proportion of patients experience persistent residual symptoms (up to 40%-50%)[ 13 , 14 ] and injury recurrence[ 6 ]. Furthermore, the prevalence of underdiagnosed injuries associated with ankle sprain, such as tendinous and osteochondral injuries and midfoot fractures are high[ 15 ]. Therefore, direct and indirect financial and societal costs for managing lateral ankle sprains and their sequelae lead to a high socioeconomic burden[ 10 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A fratura do tornozelo, considerada uma das mais comuns na traumatologia ortopédica, chega a atingir incidência de 174 fraturas por 100.000 adultos -ano 1,2 . Estima-se que o número de casos será ainda maior com o envelhecimento da população, o que torna o tratamento desta afecção muito importante tanto do ponto de vista ortopédico quanto econômico 1,3,4 .…”
Section: Introductionunclassified